El prodigio de Alemania de Calderón de la Barca y Antonio Coello: teatro y propaganda política durante la Guerra de los Treinta años - Rueda, Antonio M. (El Colegio de México, 2021)
This article examines the origin of El prodigio de Alemania (1634), a theatrical play by Calderón de la Barca and Antonio Coello that brings to the stage the dismissal and subsequent murder of Albrecht von Wallenstein, the generalissimo of the Holy Roman Empire who was accused of conspiracy during the Thirty Years War. The play, performed a few weeks after his murder, takes the form of an explanation of the unexpected events that surrounded the last months of the soldier’s life and that forced King Philip IV and the Count-Duke of Olivares to intervene to avoid losing the good reputation they had acquired over the previous years. The article argues that the play was conceived as a public statement in defense of the foreign policy decisions taken by Olivares. Using theatre as a weapon of propaganda, the play turns a unanimously applauded soldier into an enemy of the empire and a figure whose death will be used to keep alive a struggle that meant the beginning of the end of Spain’s influence as a European power.